SYSTEM FOR ACOUSTIC DIAGNOSTICS AND SYMPTOMATIC ASSISTANCE TO COVID-19 PATIENTS FOR USE IN EXTREMAL CONDITIONS "TREMBITA-CORONА NAU" - Isaienko, Volodymyr; Kharchenko, Volodymyr; Astanin, Vyacheslav; Shchegel, Ganna; Olefir, Valentyna; Olefir, Oleksii; Olefir, Andrii; Khomych, Olha; Khomych, Volodymyr (Proceedings of National Aviation University (archive), 2020)
The possibility of rapid adjustment of mass production of systems for acoustic pulmonary monitoring and symptomatic assistance to those affected by COVID-19 in the most difficult situation of the pandemic is considered.